2001
DOI: 10.1096/fj.01-0584fje
|View full text |Cite
|
Sign up to set email alerts
|

1α,25‐Dihydroxyvitamin D3modulates human adipocyte metabolism via nongenomic action

Abstract: We reported recently that suppression of the renal 1alpha,25-dihyroxyvitamin D3 (1lpha,25-(OH)2-D3) production in aP2-agouti transgenic mice by increasing dietary calcium decreases adipocyte intracellular Ca2+ ([Ca2+]i), stimulates lipolysis, inhibits lipogenesis, and reduces adiposity. However, it was not clear whether this modulation of adipocyte metabolism by dietary calcium is a direct effect of inhibition of 1alpha,25-(OH)2-D3-induced [Ca2+]i. Accordingly, we have now evaluated the direct role of 1alpha,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
162
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(172 citation statements)
references
References 44 publications
4
162
0
6
Order By: Relevance
“…18,19 In addition, 1a, 25-(OH) 2 -D 3 also plays a role in regulating human adipocyte UCP2 expression, suggesting that the suppression of 1a, 25-(OH) 2 -D 3 and the resulting upregulation of UCP2 may contribute to increased rates of energy utilization. 10,11 Accordingly, the suppression of 1a, 25-(OH) 2 -D 3 by increasing dietary calcium attenuates adipocyte triglyceride accumulation and caused a net reduction in fat mass in both mice and humans in the absence of caloric restriction, 13 a marked augmentation of body weight and fat loss during energy restriction in both mice and humans, 13,20 and a reduction in the rate of weight and fat regain following energy restriction in mice. 14 Our previous data demonstrate that 1a, 25(OH) 2 D 3 stimulates Ca 2 þ signaling and suppresses UCP2 expression on human and murine adipocytes 11,14 and suppresses UCP3 expression in skeletal muscle in mice; 14 accordingly, dietary calcium suppression of ROS production is likely due to suppression of circulating 1a, 25(OH) 2 D 3 levels and resultant reductions in Ca 2 þ signaling and increases in UCP2 and UCP3 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 In addition, 1a, 25-(OH) 2 -D 3 also plays a role in regulating human adipocyte UCP2 expression, suggesting that the suppression of 1a, 25-(OH) 2 -D 3 and the resulting upregulation of UCP2 may contribute to increased rates of energy utilization. 10,11 Accordingly, the suppression of 1a, 25-(OH) 2 -D 3 by increasing dietary calcium attenuates adipocyte triglyceride accumulation and caused a net reduction in fat mass in both mice and humans in the absence of caloric restriction, 13 a marked augmentation of body weight and fat loss during energy restriction in both mice and humans, 13,20 and a reduction in the rate of weight and fat regain following energy restriction in mice. 14 Our previous data demonstrate that 1a, 25(OH) 2 D 3 stimulates Ca 2 þ signaling and suppresses UCP2 expression on human and murine adipocytes 11,14 and suppresses UCP3 expression in skeletal muscle in mice; 14 accordingly, dietary calcium suppression of ROS production is likely due to suppression of circulating 1a, 25(OH) 2 D 3 levels and resultant reductions in Ca 2 þ signaling and increases in UCP2 and UCP3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9] These effects are mediated by suppression of 1a, 25-(OH) 2 D 3 -induced stimulation of Ca 2 þ influx and inhibition of adipocyte UCP2 gene expression. 10,11 We have also recently shown that ROS production is modulated by mitochondrial uncoupling status and cytosol calcium signaling, and that 1a, 25(OH) 2 D 3 regulates ROS production in cultured murine and human adipocytes. 12 Accordingly, we propose that 1a, 25(OH) 2 D 3 may regulate oxidative stress in adipocytes by promoting ROS production, and that modulating 1a, 25(OH) 2 D 3 through dietary calcium may affect oxidative stress in vivo.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3] We have shown that 1a, 25-dihydroxyvitamin D mediates increases in intracellular calcium ([Ca 2 þ ]i) in adipocytes via the 1a, 25-dihydroxyvitamin D-membraneassociated rapid response steroid hormone (1, 25D 3 -MARRS) binding protein, stimulates lipogenesis and inhibit lipolysis via a calcium-dependent mechanism. 4,5 We have also shown a dose-responsive inhibition of uncoupling protein 2 expression by 1a, 25-dihydroxyvitamin D in adipocytes; this is a genomic effect, presumably mediated by the nuclear vitamin D receptor (nVDR). 6 However, the presence of the nVDR in mature adipocytes and its role in adipocyte metabolism are not clear.…”
Section: Introductionmentioning
confidence: 92%
“…5,16 Conversely, the decrease in [Ca 2 þ ]i observed with increasing calcium appears attributable to suppression of circulating 1a, 25-dihydroxyvitamin D. 9,18,19 Consistent with this, data from our laboratory have demonstrated that 1a, 25-dihydroxyvitamin D induces rapid [Ca 2 þ ]i influx in adipocytes, whereas a specific membrane vitamin D receptor antagonist (1b, 25-dihydroxyvitamin D) blocked this effect. 4 This indicated a non-genomic action of 1a, 25-dihydroxy Role of 1a, 25-Dihydroxyvitamin D in adipocyte X Sun and MB Zemel vitamin D via a putative membrane vitamin receptor, which later was identified as the 1, 25D 3 -MARRS, 20 in modulating…”
Section: Role Of 1a 25-dihydroxyvitamin D In Adipocyte X Sun and Mb mentioning
confidence: 99%
“…suggested that a high-calcium diet decreases calcitriol level and that in turn inhibits intracellular Ca 2+ level, stimulating lipolysis and inhibiting lipogenesis, and leading to loss of body fat [31,32]. The reduction of waist circumference in the current study is probably associated with increased calcium intake from dairy products.…”
Section: Discussionmentioning
confidence: 51%